1981
DOI: 10.1172/jci110333
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic effects of bullous pemphigoid autoantibodies on rabbit corneal epithelium.

Abstract: A B S T R A C T Bullous pemphigoid (BP) is associated with circulating autoantibodies reactive with an antigen(s) of the basement membrane zone (BMZ) of skin and mucosae. The pathogenicity of these autoantibodies, although suspected, is unconfirmed. We have investigated the effects of BP autoantibodies on a closely related tissue, the corneal epithelium of the rabbit. IgG fractions from the sera of seven patients with BP were purified by (a) ammonium sulfate precipitation, (b) ion exchange chromatography, or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 7 publications
0
29
0
2
Order By: Relevance
“…Gammon and Briggaman (36), however, could not reproduce these findings. Our laboratory demonstrated that local intrastromal injections of BP IgG into rabbit corneas induced separation ofthe epithelium from the stroma and migration ofneutrophils into the epithelial-stromal junction (37). Contralateral corneas injected with normal human IgG showed no inflammatory changes.…”
Section: Discussionmentioning
confidence: 91%
“…Gammon and Briggaman (36), however, could not reproduce these findings. Our laboratory demonstrated that local intrastromal injections of BP IgG into rabbit corneas induced separation ofthe epithelium from the stroma and migration ofneutrophils into the epithelial-stromal junction (37). Contralateral corneas injected with normal human IgG showed no inflammatory changes.…”
Section: Discussionmentioning
confidence: 91%
“…its diagnosis. The binding of these autoantibodies to antigens located in the BMZ plays an important role in the pathogenesis ofblister formation in BP (2)(3)(4). BP antigens are normal components of the hemidesmosome complex of the BMZ, which are thought to be important not only in the pathogenesis of BP but also in dermoepidermal adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating autoantibodies target human type XVII collagen (human collagen 17 [hCOL17]), also known as BP Ag 2 (BPAG2) or BP180, which is a major component in hemidesmosome-anchoring filament complexes at the epidermal basement membrane zone (BMZ) (3)(4)(5)(6)(7)(8)(9). The major pathogenic epitope of BP autoantibodies is present at the extracellular noncollagenous 16A (NC16A) domain, which has distinctive diversity among different species (10)(11)(12). Deposition of anti-hCOL17 autoantibodies at the BMZ triggers sequential inflammatory cascades, including complement activation, degranulation of dermal mast cells, infiltration of eosinophils and neutrophils, and subepidermal blister formation elicited by proteinases derived from the inflammatory cells (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%